DEVELOPMENT OF MAHÂRAH AL-ISTIMÂ’ TEST INSTRUMENT FOR ELECTRONIC BASED ARABIC STUDENT USING THE KAHOOT! APPLICATION - Ahmad Zubaidi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This study aimed to develop the feasibility of the Mahârah al-Istimâ’ test instrument for electronic-based Arabic students using the Kahoot! application at UIN Sunan Kalijaga Yogyakarta. The method used in this research is the research and development of Borg and Gall model through analysis, design, and testing. Eligibility is based on the expert validator test and the final operation field test. The results of the study can be concluded that: 1) Preparation of the Test Instrument refers to the 5 objectives or indicators of Mahmud Kamil an-Naqah into 50 questions in product design using the Kahoot! application, 2) From the results of the expert validator it is known that the results of the material quality are obtained by an average 5.37 and the media quality of the application is obtained by an average of 4.75 (very feasible), 3) After being obtained from the main field test to 20 students there are 6 questions or 12% that are not feasible because they are invalid and have not discrimination index, then the author revise and test the revision results to 70 students with 100% valid results and are suitable for use.